2018
DOI: 10.1016/j.cbi.2017.11.018
|View full text |Cite
|
Sign up to set email alerts
|

Hesperidin attenuates iron-induced oxidative damage and dopamine depletion in Drosophila melanogaster model of Parkinson's disease

Abstract: This study has evaluated the action of flavonoid hesperidin on the neurotoxic effects caused by the intake of iron (Fe) in Drosophila melanogaster. Male adult flies, aged 1-3 days, have been divided into four groups of 50 each: (1) control, (2) Hsd 10 μM, (3) Fe 20 mM (4) Hsd 10 μM + Fe 20 mM. During the exposure protocol, the flies have been exposed to a diet containing Hsd and/or Fe for 48 h. The survival and behavioral analyses have been carried out in vivo, and ex vivo. The analyses involved acetylcholines… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(26 citation statements)
references
References 53 publications
3
21
0
Order By: Relevance
“…The blood-brain barrier regulates iron entry into the brain (Mehta et al, 2009 ), but we still do not know how iron traffics in the peripheral and central nervous systems or how Fe-S and/or Moco enzymes affect the circadian clock. Answers to questions of the basic cell biology of metal homeostasis are prerequisite for proposing better therapeutics when neuronal functions are compromised in disease (Zhu et al, 2014 ; Calap-Quintana et al, 2017 ; Ruland et al, 2017 ; Poetini et al, 2018 ).…”
Section: Physiological Relevance Of Fe-s and Moco Enzymes In Differenmentioning
confidence: 99%
“…The blood-brain barrier regulates iron entry into the brain (Mehta et al, 2009 ), but we still do not know how iron traffics in the peripheral and central nervous systems or how Fe-S and/or Moco enzymes affect the circadian clock. Answers to questions of the basic cell biology of metal homeostasis are prerequisite for proposing better therapeutics when neuronal functions are compromised in disease (Zhu et al, 2014 ; Calap-Quintana et al, 2017 ; Ruland et al, 2017 ; Poetini et al, 2018 ).…”
Section: Physiological Relevance Of Fe-s and Moco Enzymes In Differenmentioning
confidence: 99%
“…Hesperidin on the other hand, display antioxidative properties by scavenging of free radicals (Garg et al, 2001), restrain free radical synthesis and the distribution of free radical reactions through the chelation of metal (iron and copper) ions (Andjelković et al, 2006), suppresses the superoxide‐derived Fenton reaction (Mladenka et al, 2011) and augment endogenous antioxidative defense system (Poetini et al, 2018). Previous studies had indicated that treatment with flavonoids could reverse the disturbed rhythmicity of antioxidants and biochemical indices (Subramanian et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Thus by taking the sample blank reading, the level of interference is taken into consideration and brought to level zero before other readings are determined (Ingle and Crouch, 1988). Some researchers have determined both the level of malondialdehyde produced from lipid peroxidation (Ohkawa et al, 1979), a standard oxidative damage indicator and level of reactive oxygen species via oxidation of fluorescent dye 2,7-dichlorofluorescein diacetate (DCF-DA) a general index of ROS levels (Pérez-Severiao et al, 2004) using the Harwich strain of D. melanogaster (Paula et al, 2016;Saraiva et al, 2018;Poetini et al, 2018). This is supported by our findings from Table 1, in which the inhibition of GST activity may be due to the increase in the toxicity effect of 1.0% DSS.…”
Section: Discussionmentioning
confidence: 99%